Buyer Benefits in Creation of Online Buying - Bhatti, Anam; Muhammad Basit, Hafiz; mahwish Raza Naqvi, Syeda; Jahangir Muhammad Bilal, Adeel; Akram, Hamza (International Journal of Psychosocial Rehabilitation, 2020)
The main aim of this study is to examine the effect of convenience, product variety, knowledge, and ease of use on online buying in Pakistan. In this time online buying is increasing fast. The current study model developed on the basis of prior literature to determine the effect of convenience, product variety, knowledge, and ease of use on online buying. Data for this study was collected from online users by using simple random sampling. Sample size is 200. structural equation modeling (SEM) methods used for analysis. Findings of this study demonstrate that convenience and product variety have positive influence on online buying and ease of use and knowledge have no effect on online buying. Some limitations and future recommendations are mentioned in end of paper.